A journey at Mangrove Forest in south Bali: To be conserved or not to be conserved (A Review) - A.A. Putu Sri Dewi Lestari (Bali Tourism Journal, 2017)
Mangrove forests are a group of plants that grow along sub-tropical coastlines that have a special function in an environment containing salt and landscapes such as beaches with anaerobic soil reactions. In general, mangrove forests can be defined as forest types that grow in tidal areas (especially on sheltered beaches, lagoons, and river estuaries) that are flooded by tidal and free from submerged entanglement where the mangrove ecosystem is tolerant of salt.